Lanthanide Terpyridine‐Based Assemblies: Towards Dual Luminescent Probes. Issue 3 (19th January 2015) - Molloy, Jennifer K.; Pillai, Zeena; Sakamoto, Junji; Ceroni, Paola; Bergamini, Giacomo
Abstract A tetrahedral shape‐persistent molecule equipped with four terpyridine ligands can form an oligomeric structure upon complexation with metal ions, in which two terpyridine units are intermolecularly connected via a metal ion. The most interesting results were obtained upon binding of lanthanide ions, whose luminescence is sensitized by the ligand. In particular, dual luminescent probes were obtained upon concomitant complexation of two different lanthanide ions, such as EuIII and NdIII.